Atherogenic index of plasma is associated with vertebral fracture: a longitudinal study - Zhang, Xin; Xie, Pinliang; Yin, Yong; Li, Xinfeng (Frontiers in Endocrinology, 2025)
PurposeThe atherogenic index of plasma (AIP), recognized as a marker of atherosclerosis, which also has a profound impact on bone metabolism. However, research exploring the association between the AIP and the probability of vertebral fractures in populations is still relatively scarce. The study aims to evaluate the association between the AIP and vertebral fractures probability in individuals in a longitudinal study.Patients and methodsA total of 1395 subjects who were older than 55 years and underwent CT scans for lung cancer screening between July 2019 and July 2021 were enrolled and followed up for a duration ranging from 8 months to 6 years. Among them, 91 individuals experienced new vertebral fractures. Participants were stratified into four groups based on AIP quartiles. The association between the AIP and vertebral fractures probability was then assessed by cox proportional hazards model.ResultsThe incidence of vertebral fracture decreased with increasing AIP (p for trend = 0.001). Kaplan-Meier survival analysis indicated that vertebral fractures were more likely to occur in patients with low levels of AIP (log-rank, all P < 0.05). Multivariate Cox regression analysis showed that AIP was negatively associated with the probability of vertebral fractures even after accounting for confounding factors (adjusted hazard ratio (aHR) = 0.27, 95%CI = 0.10-0.71 for continuous AIP; aHR = 0.48, 95%CI = 0.26-0.90 for Q2; aHR = 0.41, 95%CI = 0.19-0.88 for Q4, respectively). Subgroup analysis showed that such associations were mainly observed in male subjects. Restricted cubic splines further showed that the probability of vertebral fracture decreased with the increasing of AIP after adjusting with confounders in overall population and men, but not in women.ConclusionOur study demonstrated a strong association between the AIP and the probability of vertebral fracture. Low AIP may be an associated factor of vertebral fracture.